Motivating Parents to Improve Children's Ability to Read and Write the Qur'an - Yudelnilastia Yudelnilastia; Ikas Lisgusni; Hoktaviandri Hoktaviandri (Khalaqa: Journal of Education and Learning, 2026)
Reading and writing the Qur'an is an obligation for every Muslim and is an important foundation in religious education from an early age. However, the reality in the field shows that parental motivation in encouraging children to learn to read and write the Qur'an is still low. This study aims to qualitatively describe the extent of parental motivation at TPQ Al-Ikhlas, Kenagarian Taratak Tinggi, Jorong Sakato, in guiding their children to read and write the Qur'an. The research method used is descriptive qualitative with observation and interview techniques, so as to obtain a comprehensive picture of the behavior, perceptions, and actions of parents towards children's learning. The results of the study indicate that parental motivation is still very low, as seen from the lack of attention to children's homework (PR), weak discipline, and indifference to Quran tuition. The main factors causing low motivation are parents' busy daily work and the assumption that the Qur'an does not provide material security for the child's future. The conclusion of this study confirms that low parental motivation has direct implications for children's Qur'an literacy skills. Therefore, efforts are needed to increase parental awareness through an educational approach and continuous guidance so that children can grow up with strong religious provisions.